Production And Purification Of Mutl Gene And Uvrd Recombinant Protein For Helicase Dependent Dna Amplification - Buskaran, Kalaivani (2015)
Kajian ini telah dijalankan untuk mengoptimumkan penghasilan rekombinan UvrD helicase dan rekombinan MutL protein untuk ujian amplifikasi helicase. Rekombinan UvrD helicase telah diklon dan diekspresikan dengan vektor Lemo21. Penghasilan UvrD helicase protein telah dioptimumkan 10% dengan menggunakan kaedah konvensional kelalang bergoncang. Penghasilan rekombinan UvrD helicase yang optimum telah berjaya dihasilkan dengan kaldu Terrific, 0.2 mM kepekatan IPTG, 9 jam masa induksi dan pada suhu 37°C selepas induksi. Penghasilan rekombinan UvrD/pET28a/Lemo21 telah dioptimumkan dengan teknik fermentasi menggunakan kelalang bergoncang skala kecil memberikan hasil protein UvrD rekombinan sebanyak 1.35 ng/μg dibandingkan dengan penghasilan 0.143 ng/μg dari kajiann awal yang dijalankan. Disamping, rekombinan UvrD helicase berjaya befungsi rekombinan MutL protein telah diasingkan dan diamplifikasikan daripada pencilan Escherichia coli tempatan. Tindak balas Berantai Polimerase mangamplifikasikan MutL protein dengan saiz 1848 bp. MutL gen kemudian diklon ke dalam vektor pengklonan TOPO PCR 2.1 This research was conducted to optimize yield of recombinant UvrD helicase and to produce recombinant MutL protein for the helicase amplification dependent reaction. Recombinant UvrD helicase were cloned and expressed into Lemo21 expression host. The overall yield of the UvrD helicase protein was improved 10% using conventional shake flask cultivation method. The optimum recombinant UvrD helicase were successfully produced in terrific broth culture medium, at 0.2 mM IPTG inducer concentration, 9 hours of post-induction time and 37°C post-induction temperature. The cultivation of the recombinant UvrD/pET28a/Lemo21 in small scale fermentation using shake flask culture has optimized the yield to 1.35 ng/μg recombinant UvrD helicase proteins as compared to 0.143 ng/μg of recombinant UvrD helicase protein from previous studies. In order for, recombinant UvrD helicase function, recombinant MutL protein was produce from local isolate of Escherichia coli. The PCR amplified MutL protein had size of 1848 bp of sequence analysis. The MutL gene was then cloned into TOPO PCR 2.1 cloning vector.